Characterization of cellulose tri acetate (CTA) forward osmosis membrane for nom removal - Mei Kei, Lai (2015)
Nowadays, to cater for the increasing population in Malaysia, drinking water is taken primarily from surface water sources like rivers, lakes, and reservoirs. These surface water sources need to be treated correctly at low cost and energy before consuming by the citizens. Among all the methods used, forward osmosis (FO) fits the best. In lieu of hydraulic pressure, forward osmosis is separation process which utilizes a highly concentrated draw solution to induce the driving force for water to permeate across the membrane. This research focuses on the characterization of Cellulose Tri Acetate (CTA) Membrane performance in forward osmosis process to treat synthesized river water containing natural organic matter (NOM) which is humic acid with concentration of 15mg/L by using sodium chloride (NaCl) solution as the draw solution. This research was conducted based on the concentration of NaCl draw solution which is a parameter that will impact the water flux and performance of forward osmosis which are humic acid rejection and reverse salt diffusion. In addition, the impact of feed solution pH on the process was investigated. The humic acid rejection was measured by UV-Vis Spectrometer while reverse salt diffusion was measured by conductivity meter. Based on the results obtained, increase in the concentration of NaOH in feed solution increases the pH which ultimately affect the water flux, humic acid rejection and reverse salt diffusion. Besides, it is shown that increase in both draw solution concentration and feed solution pH increase the water flux. The water flux obtained by using related formula showed the highest figure by 2.5M NaCl draw solution with the reading of 1.580 x 10-6 m3/m2.min for feed solution pH of 9.73 and 2.054 x 10-5 m3/m2.min for feed solution pH of 11.65. Furthermore, the increase in draw solution concentration causes a decrease in humic acid rejection for both feed solutions with pH of 11.65 showed a higher solute rejection of more than 97%. It is also shown from the result that the increase in draw solution concentration and water flux causes an increase in reverse salt diffusion for both feed solutions with pH of 9.73 showed a higher reverse salt diffusion. Based on the discussions, it is found that the optimum condition for treating river water by using CTA membrane can be achieved at high concentration of draw solution with high pH of feed solution. By completing this research, the effectiveness of using CTA membrane to treat river water in Malaysia by forward osmosis process can be investigated and the optimum condition of the process will be determined in order to overcome the problem of water depletion in Malaysia.